2022
DOI: 10.5334/cstp.469
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Diversity in Citizen Science Mosquito Surveillance: A Scoping Review

Abstract: Global concern regarding mosquito-borne disease emergence and re-emergence has driven the development of citizen science mosquito surveillance initiatives. Although these initiatives have shown great potential to assist local health authorities, ensuring outcomes are translatable to improved public health policy and practice remains challenging. Here we present a summary of citizen science mosquito surveillance programs worldwide, their focus, strategies, and outcomes, with a view to how best to apply this app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…Examples of citizen science projects to collect data about Aedes albopictus. For a review comparing these projects see[94] …”
mentioning
confidence: 99%
“…Examples of citizen science projects to collect data about Aedes albopictus. For a review comparing these projects see[94] …”
mentioning
confidence: 99%
“…The potential of iNaturalist for detecting vector species was also verified in Europe, North America, North Africa and the Middle East [19], and the results indicated that the iNaturalist platform could complement existing vector surveillance data. Citizen science initiatives on mosquito surveillance are also emerging in tropical countries and areas where dengue and malaria are endemic [22,56,57], and ethical issues were discussed in a community-based program in Nicaragua and Mexico [58]. As ethical discussions underlining communitybased research have shown, researchers should ensure that individuals and communities have the autonomy to monitor and control the vectors in their properties and have a safe space for a dialogue focusing on mutual respect and community health [58].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a citizen science approach in mosquito monitoring has been explored since 2011 [20][21][22]. It has provided opportunities to upscale geographic coverage of the traditional methods and gather real-time information related to human-mosquito encounters [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of MBDs, numerous continuing citizen science surveillance projects (29 projects operating in 16 countries all over the world, including some with wide geographic coverage) [ 26 ] have successfully involved members of the public and provided data on mosquito populations. For future improvement, there is a need to continue engaging with stakeholders, researchers, public health agents, industry, and policymakers.…”
Section: Introductionmentioning
confidence: 99%